Efficiency of Embryo Rescue Technology in St. Augustinegrass Breeding. Issue 1 (19th October 2017) - Genovesi, A. D.; Chandra, A.; Meeks, M.
Abstract : St. Augustinegrass [ Stenotaphrum secundatum (Walt.) Kuntze] is a popular warm‐season turfgrass in Gulf Coast regions of the United States. Diploid St. Augustinegrass produces fertile seed, but triploids and higher polyploids are mostly sterile. Polyploid St. Augustinegrass cultivars have been selected for their resistance to southern chinch bugs, St. Augustine Decline, and drought tolerance but lack the cold hardiness and shade tolerance of diploids. However, because of sterility barriers, the polyploid germplasm had not been fully used as breeding material until 2009 when we reported the development of interploid hybrids using embryo rescue technology. The objective of the present study was to backcross these first‐generation interploid hybrids with diploid males to produce second‐generation hybrids. Sterility barriers were found to be much greater with second‐generation crosses yielding only 0.00 to 2.69% progeny per interploid hybrid. Using this technique, the embryos are generally rescued 3 wk postpollination, thereby causing a heavy demand on one's time to process spikelets before embryos abort. Our preliminary findings show the use of cold storage at 7°C to potentially extend the processing period up to 2 mo with a slight drop off in efficiency (4.37–6.03% crossability). Our results also show the potential of first‐generation hybrids to exhibit superior performance under drought when compared with diploid cultivars Palmetto and Raleigh. Tested second‐generation interploids did not exhibit superior performance in drought. Nonetheless, our results emphasize the utility of embryo rescue technology in facilitating gene exchange between ploidy levels to generate hybrids with superior performance.